Impact of high-speed rail on the operational capacity of conventional rail in China. (September 2021) - Cheng, Junmei; Chen, Zhenhua
Abstract: Although many studies have evaluated the impact of high-speed rail (HSR) development on transportation connectivity and accessibility, it remains unclear to what extent the introduction of HSR may influence the operational capacities of freight and conventional passenger rail services. This paper addresses this question by examining the spatial and temporal variations of transport capacities of different rail systems. In addition, the interaction effects of different rail systems were investigated using a structural equation model. The results reveal that the spatial and temporal evolution of operational capacity varies significantly among freight, conventional passenger, and high-speed passenger rail systems. Moreover, HSR was found to have a substitutional effect on conventional passenger rail, although the effects vary spatially in different corridors. Furthermore, the operational capacity of conventional passenger rail is negatively associated with that of freight rail, which confirms that a service cut in conventional passenger rail contributes to an increase in the capacity of freight rail. The analysis also demonstrates that HSR promotes the expansion of freight rail capacity through its substitutional effect on conventional passenger rail. These findings provide important implications for transportation planners to optimize operational plans, in order to improve the performance of various rail services.